The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1038/sj.leu.2402959
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of minimal residual disease (MRD) by real-time quantitative reverse transcription PCR (RQ-RT-PCR) in childhood acute myeloid leukemia with AML1/ETO rearrangement

Abstract: The fusion transcript AML1/ETO corresponding to translocation t(8;21)(q22;q22) can be found in approximately 7-12% of childhood de novo AML. Despite the favorable prognosis, some of these patients relapse. Most of MRD studies so far were performed on adults treated not uniformly. Therefore, we analyzed the follow-up of 15 AML1/ETO-positive children using real-time quantitative reverse transcription PCR (RQ-RT-PCR), all enrolled in the multicenter therapy trial AML-BFM 98. AML1/ ETO copy numbers were normalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 37 publications
3
49
0
2
Order By: Relevance
“…The protocol will prospectively evaluate the prognostic importance of in vitro drug resistance and MRD levels at different time points. [27][28][29] This may help us to identify new subgroups in AML, which may benefit from different therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol will prospectively evaluate the prognostic importance of in vitro drug resistance and MRD levels at different time points. [27][28][29] This may help us to identify new subgroups in AML, which may benefit from different therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, recently, several studies strongly suggested that RQ-RT-PCR might be a more valuable technique to predict relapse in AML with core binding factor (CBF) rearrangement in general or in t(8;21) AML. 13,14,[25][26][27] In those studies, critical thresholds of MRD levels, which could distinguish between patients at risk of relapse and those in continuous CR, were identified. In the present study, no pretreatment characteristics were predictive of the outcome, possibly due to the relatively low number of patients.…”
Section: Prognostic Value Of Rq-pcr In Amlmentioning
confidence: 99%
“…3 A study in childhood AML of 15 patients also showed that RUNX1-RUNX1T1 increased transcript levels are predictive of relapse. 188 MLL fusion transcripts for MRD monitoring have also been analyzed in 19 patients with t(9;11)(q22;q23) AML. Eleven of these patients showed negative PCR for the MLL fusion transcripts, and this associated with a better outcome.…”
Section: Rq-pcrmentioning
confidence: 99%